Cyclists in shared bus lanes: could there be unrecognised impacts on bus journey times?. Issue 3 (5th September 2017) - Aldred, Rachel; Best, Luke; Jones, Phil
Abstract : This paper contributes to debates around improving the modelling of cycles, through an exploratory case study of bus–cycle interactions in London. This case study examines undocumented delays to buses caused by high volumes of cyclists in bus lanes. It has generally been assumed that cyclists do not noticeably delay buses in shared lanes. However, in many contexts where cyclists routinely share bus lanes, cyclist numbers have historically been low. In some such places, bus lanes are now seeing very high volumes of cyclists, far above those previously studied. This may have implications for bus – and cycle – journey times, but traditionally traffic modelling has not represented the effects of such interactions well. With some manipulation of parameters taken from models of other cities, the model described here demonstrates that cycles can cause significant delays to buses in shared lanes, at high cycling volumes. These delays are likely to become substantially larger if London's cycling demographic becomes more diverse, because cyclist speeds will decline. Hence bus journey time benefits may derive from separating cycles from buses, where cycle flows are high. The project also suggests that microsimulation modelling software, as typically used, remains problematic for representing cyclists.